O Big Data na produção científica da Ciência da Informação - Luiz Carlos Felipe de Oliveira (2017)
The large amount of structured and unstructured data present in our days called Big Data constitute demands for information professionals and research for information science. However, it has been observed that other areas have been appropriated to the study and use of the phenomenon with more agility than the information science. To help understand how information science has incorporated Big Data, this research has the objective of studying the approach that information science attributes to the theme through the analysis of its scientific production. In the literature review are treated the emergence of large volumes of data, the called e-science, data science, data scientist and the consequences experienced by information science and information scientist. Data collection was done through a bibliographical research to identify the scientist production on the topic Big Data in the area of information science. Teachers, programs, universities, countries, and approaches were identified through the analysis of the bibliographic records of the scientific production on the theme Big Data in the area of information science. The data were analyzed quantitatively and qualitatively. The results present the mapping of how this science has approached the theme Big Data in a ranking of universities/entities, training programs, authors and countries.